2014
DOI: 10.5935/1678-9741.20140043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peripheral Muscle Strength of Patients Undergoing Elective Cardiac Surgery: A Longitudinal Study.

Abstract: IntroductionPeripheral muscle strength has been little explored in the literature in the context of cardiac rehabilitation.ObjectiveTo evaluate the peripheral muscle strength of patients undergoing elective cardiac surgery.MethodsThis was a longitudinal observational study. The peripheral muscle strength was measured using isometric dynamometry lower limb (knee extensors and flexors) at three different times: preoperatively (M1), the day of discharge (M2) and hospital discharge (M3). Participants received phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
10
0
4
Order By: Relevance
“…CR is a critical component of post-operative therapy for CAD patients [35,36,37]. Longitudinal research has found lower limb strength to be compromised after cardiac surgery compared with pre-operative levels but steadily improves with values reaching close to baseline at hospital discharge [38]. The results of the present study confirm the benefits of CR, particularly within the domain of lower limb function after CABG with saphenous vein harvesting.…”
Section: Discussionsupporting
confidence: 73%
“…CR is a critical component of post-operative therapy for CAD patients [35,36,37]. Longitudinal research has found lower limb strength to be compromised after cardiac surgery compared with pre-operative levels but steadily improves with values reaching close to baseline at hospital discharge [38]. The results of the present study confirm the benefits of CR, particularly within the domain of lower limb function after CABG with saphenous vein harvesting.…”
Section: Discussionsupporting
confidence: 73%
“…A reduction in oxidative capacity and a significant decrease in blood flow affect the production of energy in the muscle. The Brazilian version of the DASI is a valid, reliable and easily administered instrument for self-assessing functional capacity in patients with cardiovascular diseases (2,14,29).…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical manifestations result from atherosclerotic processes such as cerebrovascular disease, peripheral vascular disease, cardiac ischemia and coronary atherosclerotic disease or coronary artery disease (CAD) (1,2). Smoking, high levels of low density lipoprotein (LDL), low levels of high density lipoprotein (HDL), diabetes mellitus, systemic arterial hypertension, family history, lifestyle, obesity, sedentary lifestyle and heavy alcohol intake are the main risk factors that contribute to the development of the disease (3 -5).…”
Section: Introductionmentioning
confidence: 99%
“…The isometric muscle strength of the foot invertors, evertors and finger flexor muscles was measured using a Manual Muscle Tester (model 01163 Lafayette). The participants were asked to carry out three maximal isometric contractions for each muscle group, with an interval of 60 s. The mean peak force was recorded by the muscle tester device (kg) [13].…”
Section: Assessment Of Muscle Strengthmentioning
confidence: 99%